Mobile Banking Service Quality, Perceived Security, and Continued Usage Intention among Thai Consumers: The Moderating Role of Privacy Concern - Somsak Kittisak Somsak Kittisak; Kanya Rattanapong Kanya Rattanapong; Sokha Chan Sokha Chan (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2025)
Mobile banking has become a primary channel for everyday financial transactions in Southeast Asia, yet sustained usage is shaped not only by functional features but also by the credibility of service delivery and the perceived safety of digital interactions. This study examines how mobile banking service quality influences continued usage intention among Thai consumers through perceived security and trust, while assessing whether privacy concern weakens key relationships. Building on the DeLone and McLean Information Systems Success logic, technology trust theory, and perceived risk perspectives, the research conceptualizes service quality as a multidimensional construct comprising system quality, information quality, and responsiveness. Survey data were collected from 512 mobile banking users across four Thai provinces representing different levels of urban density. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test direct effects, serial mediation, and moderation. The results indicate that service quality strengthens perceived security and trust, which in turn increase continued usage intention; privacy concern dampens the translation of perceived security into trust and reduces the strength of the trust–intention link. The findings extend digital finance research by clarifying why convenience-driven adoption does not guarantee retention, highlighting the importance of security perceptions and privacy-sensitive design. Policy implications emphasize transparent communication, incident-response readiness, and consumer literacy interventions that reduce privacy anxiety without normalizing risky behavior.